Synthesis of Novel N1 and N2 Indazole Derivatives - Prasanna Bethanamudi; Srinivas Bandari; Kanakaraju Sankari; Amarnath Velidandi; G. V. P. Chandramouli (E-Journal of Chemistry)
The alkylation of 5-cyano indazoles 2 in the presence of readily available imidizolium salts (ionic liquids) (Bmim)BF4 as phase transfer catalyst were performed to afford the regio isomers N1-and N2-(substituted alkyl)-5-cyano indazoles. The N1-alkylated cyano indazoles were converted to the corresponding N1-(substituted alkyl)-5-aminomethyl and 5-carbaldehydes 5(a-f) and 6(a-f).